REDESCRIPTION AND PHYLOGENETIC RELATIONSHIPS OF THE PROTEROCHAMPSID RHADINOSUCHUS GRACILIS (DIAPSIDA: ARCHOSAURIFORMES) FROM THE EARLY LATE TRIASSIC OF SOUTHERN BRAZIL (Ameghiniana, 2015)
The proterochampsids are small to medium-sized, quadrupedal and probable semi-aquatic reptiles that were part of the evolutionary radiation of Archosauromorpha during the Triassic. The group is restricted to the Middle and Late Triassic of South America with eight nominal species. Rhadinosuchus gracilis Huene was the first described proterochampsid and comes from the late Carnian–earliest Norian of southern Brazil. This genus and species is currently the most enigmatic and poorly known member of the group. For this reason we redescribe here its anatomy and discuss its phylogenetic relationships. We found that this species can be distinguished from other proterochampsids and we dismiss the proposed synonymy with Cerritosaurus binsfeldi Price. Our quantitative phylogenetic analysis found Rhadinosuchus gracilis more closely related to Gualosuchus reigi Romer and Chanaresuchus bonapartei Romer than to other proterochampsids, together forming the subfamily Rhadinosuchinae. Characters supporting this assignment include a maxilla with a distinct longitudinal change in slope between lateral and dorsal surfaces, and dorsal surface of nasal and frontal ornamented by ridges showing a radial pattern. In addition, Rhadinosuchus gracilis was recognized as the sister taxon of Chanaresuchus bonapartei based on a lacrimal with an antorbital fossa that occupies almost half or more of the anteroposterior length of the ventral process. The topology of the phylogenetic analysis shows that the Brazilian species do not form a monophyletic clade and favours multiple dispersal events between the Ischigualasto-Villa Unión (northwestern Argentina) and the Paraná (southern Brazil) basins.Resumen. REDESCRIPCIÓN Y RELACIONES FILOGENÉTICAS DEL PROTEROCHÁMPSIDO RHADINOSUCHUS GRACILIS (DIAPSIDA: ARCHOSAURIFORMES) DEL TRIÁSICO TARDÍO TEMPRANO DEL SUR DE BRASIL. Los proterochámpsidos son reptiles cuadrúpedos, de pequeño a mediano tamaño y probablemente semiacuáticos que fueron parte de la radiación evolutiva de los Archosauromorpha durante el Triásico. El grupo esta restringido al Triásico Medio y Tardío de América del Sur, con ocho especies nominales. Rhadinosuchus gracilis Huene fue el primer proterochámpsido descripto y proviene del Carniano tardío–Noriano más temprano del sur de Brasil. Este género y especie es actualmente el más enigmático y menos conocido de los miembros del grupo y, como resultado, redescribimos aquí su anatomía y discutimos sus relaciones filogenéticas. Encontramos que esta especie puede ser distinguida de otros proterochámpsidos y rechazamos su supuesta sinonimia con Cerritosaurus binsfeldi Price. Nuestro análisis filogenético cuantitativo encontró a Rhadinosuchus gracilis como más cercanamente relacionado a Gualosuchus reigi Romer y Chanaresuchus bonapartei Romer que a otros proterochámpsidos, juntos formado la subfamilia Rhadinosuchinae. Los caracteres que soportan esta asignación incluyen un maxilar con un claro cambio de pendiente entre las superficies lateral y dorsal, y un nasal y frontal con superficies dorsales ornamentadas por crestas dispuestas en un patrón radial. Adicionalmente, Rhadinosuchus gracilis fue encontrado como el taxón hermano de Chanaresuchus bonapartei basado en un lacrimal con una fosa anteorbitaria que ocupa casi la mitad o más del largo anteroposterior del proceso ventral. La topología del análisis filogenético muestra que las especies brasileñas no forman un clado monofilético entre sí e indica la presencia de múltiples eventos dispersivos entre las cuencas de Ischigualasto-Villa Unión (noroeste de Argentina) y de Paraná (sur de Brasil).